Review: Tablet Effervescent dari Ekstrak Daun Alpukat (Persea americana Mill.) sebagai Peluruh Batu Ginjal pada Tikus Jantan Galur Wistar (Ratus norvegicus) - Naripradnya, Putu Saradevi; Eka Indra Setyawan; I Gusti Ngurah Agung Dewantara Putra (Program Studi Akuntansi IKOPIN, 2022)
Kidney stones are a health disorder characterized by the appearance of stones in the uropoetic system. Kidney stones can cause infection and cause inflammation so that they can interfere with the smooth flow of urine. If urine flow is obstructed and there is accumulation of urine in the kidneys, it will cause a decrease in the physiological function of the kidneys. The purpose of this review journal is to determine the formulation and evaluation of avocado leaf effervescent tablets (Persea americana Mill.), The method of kidney stone decay test from avocado leaf effervescent tablets (Persea americana Mill.) In test animals, kidney stone decay test results from tablets. avocado leaf effervescent (Persea americana Mill.) in test animals, as well as the most effective dose used in the decay of kidney stones from avocado leaf effervescent tablets (Persea americana Mill.). Avocado leaves can be made as effervescent tablets to shed kidney stones because they dissolve more easily, are absorbed more quickly, and are more stable when compared to liquid preparations. Therefore, avocado leaf extract can be made into effervescent tablets to treat kidney stones.